A Gene Expression Panel is Accurate for Diagnosis and Monitoring Treatment of Eosinophilic Esophagitis in Adults - Dellon, Evan S (Clin Transl Gastroenterol, 2017)
OBJECTIVE: Eosinophilic esophagitis (EoE) can be difficult to diagnose. We aimed to evaluate whether a gene expression score could differentiate adult EoE cases from non-EoE controls and to determine whether scores normalized after treatment for EoE. METHODS: We analyzed prospectively collected esophageal biopsies from EoE patients (diagnosed as per consensus guidelines and after a proton pump inhibitor trial) and non-EoE controls. Gene expression for a previously constructed 94 gene panel was quantified for a single RNA-later preserved biopsy. For diagnosis, a summary expression score and the area under the receiver operating characteristic curve (AUC) were calculated. For treatment response (defined as <15 eosinophils per high-power field), pretreatment and posttreatment EoE samples were compared. RESULTS: For 91 EoE cases and 174 controls, gene scores for EoE cases were lower than non-EoE controls (mean 198 vs. 420; P<0.001), with an AUC of 0.927. A score ≤263 yielded a positive predictive value=91% a score ≥349 yielded a negative predictive value=90% only 12% of subjects had an indeterminate score (264–348) by this classification scheme. For the 89 EoE cases with paired pretreatment and posttreatment samples, overall gene scores improved after treatment from 199 to 343 (P<0.001). This normalization was seen only in cases with histological response (202 vs. 425; P<0.001); scores were unchanged in non-responders (189 vs. 226; P=0.25). CONCLUSIONS: A gene expression score has high diagnostic utility for distinguishing EoE patients from non-EoE controls in adults and can be used in clinical algorithms. Because it is highly responsive to treatment, the test could be used to monitor disease status.